2018
DOI: 10.5194/esurf-6-923-2018
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Increasing vertical attenuation length of cosmogenic nuclide production on steep slopes negates topographic shielding corrections for catchment erosion rates

Abstract: Abstract. Interpreting catchment-mean erosion rates from in situ produced cosmogenic 10Be concentrations in stream sediments requires calculating the catchment-mean 10Be surface production rate and effective mass attenuation length, both of which can vary locally due to topographic shielding and slope effects. The most common method for calculating topographic shielding accounts only for the reduction of nuclide production rates due to shielding at the surface, leading to catchment-mean corrections of up to 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Cosmogenic nuclide exposure dating is based on the study of rare isotopes produced by high-energy cosmic radiation breaking up the atoms that make up the minerals and rocks at the Earth's surface. The term "in situ" is used to distinguish these isotopes from those that are produced through the same cosmic-ray-induced nuclear reactions in the atmosphere -termed "meteoric" (Dunai, 2010;Granger et al, 2013). Several of the in situ cosmogenic nuclides, including the stable 3 He and 21 Ne, and the radioactive 10 Be, 26 Al, and 36 Cl, are now routinely measured and have been used in geomorphological studies for the last three decades (Bierman and Nichols, 2004;von Blanckenburg, 2005;Dunai, 2010;Granger and Schaller, 2014).…”
Section: Inferring Denudation Rates From Cosmogenicmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmogenic nuclide exposure dating is based on the study of rare isotopes produced by high-energy cosmic radiation breaking up the atoms that make up the minerals and rocks at the Earth's surface. The term "in situ" is used to distinguish these isotopes from those that are produced through the same cosmic-ray-induced nuclear reactions in the atmosphere -termed "meteoric" (Dunai, 2010;Granger et al, 2013). Several of the in situ cosmogenic nuclides, including the stable 3 He and 21 Ne, and the radioactive 10 Be, 26 Al, and 36 Cl, are now routinely measured and have been used in geomorphological studies for the last three decades (Bierman and Nichols, 2004;von Blanckenburg, 2005;Dunai, 2010;Granger and Schaller, 2014).…”
Section: Inferring Denudation Rates From Cosmogenicmentioning
confidence: 99%
“…The term "in situ" is used to distinguish these isotopes from those that are produced through the same cosmic-ray-induced nuclear reactions in the atmosphere -termed "meteoric" (Dunai, 2010;Granger et al, 2013). Several of the in situ cosmogenic nuclides, including the stable 3 He and 21 Ne, and the radioactive 10 Be, 26 Al, and 36 Cl, are now routinely measured and have been used in geomorphological studies for the last three decades (Bierman and Nichols, 2004;von Blanckenburg, 2005;Dunai, 2010;Granger and Schaller, 2014). Of these nuclides, however, 10 Be produced in quartz is the workhorse for in situ applications, and most in situ cosmogenic nuclide studies have used 10 Be either alone or in conjunction with other cosmogenic nuclides such as 26 Al and 21 Ne.…”
Section: Inferring Denudation Rates From Cosmogenicmentioning
confidence: 99%
“…More sophisticated versions of the stream power model may explicitly account for different controls in K (e.g. DiBiase and Whipple, 2011;Campforts et al, 2020;Zondervan et al, 2020b), yet such an approach requires specific data of an adequate resolution, such as river hydraulic geometry, rock strength measurements, and hydrological data to resolve spatial and temporal runoff variability, which are not readily available.…”
Section: Lithological Strength and Fluvial Erosion Efficiency In The Qfmentioning
confidence: 99%
“…Cosmic ray shielding generally reduces surface production rate ' ( , ) but extends the free path attenuation length by the change of irradiation geometry (Dunne et al, 1999). DiBiase ( 2018) evaluated the counter-effects of shielding on catchment-wide production rate (via spallation) and attenuation length, although he found that the combined shielding effect on surface production rate (via spallation) and free path attenuation length is negligible when the valley surface slope is less than 30 degrees (DiBiase, 2018). In general, shielding calculations for detrital CRN data are not very important as most shielding is local, i.e.…”
Section: Catchment Average Erosion Rates From Cosmogenic Nuclide Concentrationmentioning
confidence: 99%